2017
DOI: 10.1007/s11596-017-1778-9
|View full text |Cite
|
Sign up to set email alerts
|

Morphological features of complex congenital cardiovascular anomalies in fetuses: as evaluated by cast models

Abstract: Accurate prenatal diagnosis of complex congenital cardiovascular anomalies, vascular ones in particular, is still challenging. A fetal cardiovascular cast model can provide a copy of the cardiac chambers and great vessels with normal or pathological structures. This study was aimed to demonstrate three-dimensional anatomy of complex congenital cardiovascular anomalies in fetuses by means of corrosion casting. Twenty fetuses with prenatal-ultrasound-diagnosed complex cardiovascular anomalies were enrolled in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…This method can display the three-dimensional (3D) morphology of fetal severe CHDs. Its unique advantages will help to improve the understanding of fetal cardiac anatomy and the accuracy of prenatal diagnosis 5,6 . This study indicated cast models could vividly reveal the origin, course, dimension and spatial relationship of ductus arteriosus and other great vessels.…”
Section: Discussionmentioning
confidence: 99%
“…This method can display the three-dimensional (3D) morphology of fetal severe CHDs. Its unique advantages will help to improve the understanding of fetal cardiac anatomy and the accuracy of prenatal diagnosis 5,6 . This study indicated cast models could vividly reveal the origin, course, dimension and spatial relationship of ductus arteriosus and other great vessels.…”
Section: Discussionmentioning
confidence: 99%
“…A vascular corrosion cast is a relatively advanced technique for making anatomical vascular specimens . It can vividly display the actual geometry of the cardiac cavities and vascular lumens, and it is suitable for demonstrating complex congenital cardiovascular malformations. In our study, vascular casting was performed in one case of CPVA (Figure ), which allowed a clear grasp of the complex malformation with a more comprehensive understanding of the three‐dimensional structures than allowed by conventional cardiac autopsy.…”
Section: Discussionmentioning
confidence: 99%
“…In case 3, postnatal echocardiography also confirmed the prenatal diagnosis of a PA sling and other associated cardiac anomalies. In our previous study, we applied cardiovascular casts to display 3‐dimensional anatomy of fetal congenital cardiovascular anomalies . In case 2, not only the cardiac chambers and great vessels but also the trachea were cast with different colors.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we applied cardiovascular casts to display 3-dimensional anatomy of fetal congenital cardiovascular anomalies. 8,9 In case 2, not only the cardiac chambers and great vessels but also the trachea were cast with different colors. The cast vividly showed the interrelationship between the PA branches and trachea.…”
Section: Discussionmentioning
confidence: 99%